Design of Smart Aggregates: Toward Rapid Clinical Diagnosis of Hyperlipidemia in Human Blood. Issue 49 (31st October 2022) - Sun, Feiyi; Zhao, Wei; Shen, Hanchen; Fan, Ni; Zhang, Jianyu; Liu, Qingqing; Xu, Changhuo; Luo, Jiaming; Zhao, Mengying; Chen, Yuyang; Lam, Kristy W. K.; Yang, Xueqin; et al.
Abstract: Molecular aggregates with environmental responsive properties are desired for their wide practical applications such as bioprobes. Here, a series of smart near‐infrared (NIR) luminogens for hyperlipidemia (HLP) diagnosis is reported. The aggregates of these molecules exhibit a twisted intramolecular charge‐transfer effect in aqueous media, but aggregation‐induced emission in highly viscous media due to the restriction of the intramolecular motion. These aggregates, which can autonomously respond to different environments via switching the aggregation state without changing their chemical structures are described, as "smart aggregates". Intriguingly, these luminogens demonstrate NIR‐II and NIR‐III luminescence with ultralarge Stokes shifts (>950 nm). Both in vitro detection and in vivo imaging of HLP can be realized in a mouse model. Linear relationships exist between the emission intensity and multiple pathological parameters in blood samples of HLP patients. Thus, the design of smart aggregate facilitates rapid and accurate detection of HLP and provides a promising attempt in aggregate science. Abstract : A series of near‐infrared (NIR) luminogens for hyperlipidemia (HLP) diagnosis is reported. They can act as "smart aggregates" and autonomously respond to HLP to realize in vitro detection and in vivo imaging in mice and human blood. Intriguingly, these luminogens demonstrate NIR‐II and NIR‐III luminescence with ultralarge Stokes shifts (>950 nm).